Cerebrovascular Function in Hormonal Migraine: An Exploratory Study - Dzator, Jemima S. A.; Howe, Peter R. C.; Griffiths, Lyn R.; Coupland, Kirsten G.; Wong, Rachel H. X. (Frontiers in Neurology, 2021)
Background: Migraineurs, particularly young premenopausal women, are at increased risk of cerebrovascular disease; however, there is currently limited evidence as to whether menstrual migraine is associated with poor cerebrovascular function. Objectives: The objectives of this study were to: 1) investigate the potential association of cerebrovascular function with menstrual migraine, 2) assess migraine-related disability and quality of life in menstrual migraineurs and 3) determine whether the migraine-related disability and/or quality of life of menstrual migraineurs is associated with cerebrovascular function. Method: A cross-sectional study was undertaken in 50 menstrual migraineurs (mean age: 38.7 ± 8.2 years) and 29 controls (mean age: 35.6 ± 9.6 years). Data was collected from all participants when they were free from migraine and not menstruating. Transcranial Doppler ultrasound was used to measure resting blood flow velocity and cerebrovascular responsiveness (CVR) to hypercapnic and cognitive stimulation (neurovascular coupling) in the left and right middle cerebral artery (MCA). Additionally, menstrual migraineurs completed three questionnaires to assess migraine-related disability and quality of life as well as migraine frequency and intensity: Headache Impact Test-6™, Migraine-Specific Quality of Life and Migraine Disability Assessment. Results: Menstrual migraineurs had lower resting mean blood flow velocity (MBFV) (P=0.009) and neurovascular coupling during cognitive stimulation (P=0.010) in the left MCA than controls. No such differences were found in the right MCA. Additionally, heart rate (P=0.004) was higher in menstrual migraineurs than controls. However, no differences in CVR to hypercapnia were found between menstrual migraineurs and controls. No meaningful associations between migraine-related disability or quality of life and cerebrovascular function in menstrual migraineurs were found. Conclusions: This is the first study to show that menstrual migraineurs have poorer cerebrovascular function, as represented by lower resting MBFV and impaired neurovascular coupling in the left MCA. Future studies should investigate whether improving cerebrovascular function can prevent menstrual migraine and improve quality of life.